PERANAN PELAKSANAAN ASAS IKTIKAD BAIK DALAM HUKUM PERJANJIAN - Ibnu A'thillah Farhan; Moh. Safil Kafi (JURNAL ILMIAH RESEARCH STUDENT, 2023)
The purpose of this research is to explore the role played by the implementation of the principle of good faith in contract law, focusing on its impact on the judiciary, the effectiveness of agreements and dispute resolution. This research method uses a qualitative approach with a literature study. The result of the research is that the role of the implementation of the principle of good faith in treaty law shows the importance of ethical values and justice in forming, executing, and resolving agreements. The principle of good faith is not only the basis for maintaining the integrity and sustainability of the contract, but also serves as a counterweight to the interests of the parties, encouraging a balanced distribution of benefits and creating a stable business environment.